Connection, connectivity and choice: Learning during COVID‐19 restrictions across mainstream schools and Flexible Learning Programmes in Australia. Issue 1 (28th June 2022) - Plage, Stefanie; Cook, Stephanie; Povey, Jenny; Rudling, Emily; te Riele, Kitty; McDaid, Lisa; Western, Mark
Abstract: The COVID‐19 pandemic and associated school closures may have constrained educational participation particularly for students in disadvantaged circumstances. We explore how 30 disadvantaged students in secondary school (14 mainstream/16 Flexible Learning Programme) from Queensland, New South Wales and Tasmania experienced home learning during the first wave of COVID‐19, teasing out nuances across two educational models. Drawing on semi‐structured interviews with these students, our analysis revealed three interconnected themes inflecting their learning: connection, connectivity and choice. Connection captures the desire for belonging and practices that facilitated meeting this desire during system‐wide disruptions to school routines and face‐to‐face learning. Connectivity captures the impact of digitally facilitated learning at home on students' ability to engage with curriculum content and with their learning community. Choice captures the availability of viable options to overcome barriers students encountered in their learning and possibilities to flexibly accommodate student preferences and learning needs. Students from Flexible Learning Programmes appeared generally better supported to exercise agency within the scope of their lived experience of home‐based learning. Findings indicate a need for strengthening student‐centred policy and practices aimed at leveraging the affordances of information technology, balancing self‐directed and structured learning and providing holistic support to enable meaningful student choice.